Analisis Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Kerja Guru terhadap Komitmen Kerja Guru (Studi Kasus: SDIT Ummul Quro’Kota Bogor) - Rizqiani, Arifah; Syamsun, Muhammad; Dirdjosuparto, Sukiswo (Universitas Brawijaya, Indonesia, 2014)
The success of national education goals in particular should pay attention to the educational component of human resources. One effort to improve the quality of schools can be done by strengthening teacher's work commitment with taking into account the principal's leadership and work motivation of teachers. Based on these problems, this study aims to determine and analyze influence of principal leadership and work motivation of teachers to work commitment of teachers in SDIT Ummul Quro'in the Bogor. Instrument testing methods used SPSS software 16.00 and the hypothesis testing used structural equation model (SEM) with Smart PLS software. Characteristics of teacher respondents SDIT Ummul Quro'is dominated by women, married, educated bachelor, aged 30-39 years and has worked in SDIT Ummul Quro'for 8-15 years. One way ANOVA test results and treatment outcome descriptive that there was no difference in the commitment of teachers working for gender, age, education level, marital status and duration of work.The results of frequency distribution shows that the majority of respondents have a good perception on school leadership, teacher work motivation and work commitment of teachers. Based on the analysis of SEM with PLS approach, it is known that principal leadership significantly influence teacher's commitment to work, either directly or through the first teacher work motivation. Furthermore, in Model 1 principal leadership variables significantly influence the work motivation of teachers and the work motivation of teachers was ultimately significantly affect teacher's work commitments. It can be concluded that the principal leadership variables and the work motivation of teachers significantly influence teacher's work commitments.